Feasibility of waste to energy conversion in Bangladesh - Alam, Md Nahian Ibne; Ahmed, Wakil; Badhon, S.M. Shams Islam (2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.